Reducing nutrient loss in drainage from tomato grown in free-draining substrate in greenhouses using dynamic nutrient management - J. Cedeño; J.J. Magán; R.B. Thompson; M.D. Fernández; M. Gallardo (Agricultural Water Management, 2023)
Substrate-grown crops represent approximately 10% of the cropping area of intensive greenhouse horticulture in southern Spain. The vast majority are free draining, in that they do not collect and recirculate drainage. The substantial nutrient loss in drainage contributes to contamination of water bodies. This study examined the effectiveness of dynamic management approaches to appreciably reduce the large nutrient loss associated with free-draining substrate-grown crops. For three tomato crops, grown in substrate, this study (i) compared management of N, P and K based on the ratio of the concentration in drainage to that in the nutrient solution, to conventional management, (ii) derived uptake concentration values for N, P and K throughout the crop cycle, and (iii) evaluated uptake concentration as a nutrition management tool. Ratio-based management reduced the amounts of N, P and K in drainage, in relation to conventional management by 58–61%, 65–80% and 55–77% respectively. The amounts of applied N, P and K were reduced by 22–28%, 37–43%, and 28–34% compared to conventional management. N, P and K concentrations in the applied nutrient solution slightly below the uptake concentration were associated with much lower concentrations in the drainage solution. In contrast, when the applied nutrient concentration exceeded the uptake concentration this was associated with much higher drainage nutrient concentrations. In conclusion, the two nutritional management strategies examined, ratio-based management, and use of uptake concentrations were both associated with reduced nutrient application and a considerable reduction of nutrient loss in drainage. Fruit production was maintained with the improved nutrient management practices. These strategies offer approaches that can considerably reduce the substantial nutrient loss in drainage associated with free-draining substrate cropping in greenhouse production in southern Europe.